Promotion Strategy of Borobudur World Cultural Heritage Site for International Tourists - Surya Diarta, I Ketut (Udayana Journal of Social Sciences and Humanities; Vol 1 No 2 (2017): UJoSSH, September 2017DO - 10.24843/UJoSSH.2017.v01.i02.p12, 2017)
The poor promotion strategies of Borobudur caused the low international tourists’ arrival. Therefore, this study aimed to develop promotion strategies for the Borobudur world cultural heritage site as a tourist attraction for foreign tourists. Respondents were selected by accidental sampling of 50 tourists combined with FGD of local tourism stakeholders. Data were analyzed using descriptive qualitative method and SWOT analysis. The results showed that: (1) Strategy SO can be reached by public relations by making online publicity and using endorser to reach international coverage, (2) Strategy WO achieved through the financial support for advertising, sales promotion, personal selling, and direct marketing ( 3) Strategies ST approached with the digital promotion supported by strong branding and assisted personal selling and direct marketing, and (d) Strategies WT by promoting Borobudur market in Asia, America, and especially Australia through increasing frequency of sales promotio.n and direct marketing supported by advertising to the target market.